Dynamics of Local Melayu Language Wisdom and Social Changes in 3 Provinces: Yala, Pattani, Narathiwat, and Southern Border Provinces of Thailand - Warisah Wanaeloh; Aidinil Zetra; Indah Adi Putri (Eduvest - Journal of Universal Studies, 2024)
This research investigates the development of the Local Melayu Language in three provinces: Yala, Pattani, and Narathiwat in the Southern Border Provinces of Thailand. It focuses on the dynamics of Local Melayu Language wisdom amidst social and cultural changes and explores methods for preserving and promoting this valuable linguistic heritage. The study employs interviews and participatory observations as data collection tools. The participants, chosen through purposive sampling, include 30 key informants such as local wisdom scholars, language experts, and villagers familiar with the language structure in these provinces. The collected data were analyzed and synthesized through interpretation and conclusions aligned with the research objectives. The findings reveal that the Local Melayu Language is closely linked with societal changes, including cultural, economic, political, and administrative factors. The study emphasizes the importance of preserving and revitalizing the Local Melayu Language, including its script, such as the Jawi script, to ensure its continued presence in the communities of Yala, Pattani, and Narathiwat. Language and script are regarded as the intellectual heritage of these communities. The family institution plays a crucial role in instilling the significance of the Local Melayu Language in children and addressing any stigma associated with its use. Additionally, societal attitudes towards speakers of the Local Melayu Language should be positive, promoting respect and recognition of the language's value. This research underscores the necessity of safeguarding the Local Melayu Language as an essential cultural asset in the Southern Border Provinces of Thailand.